1990
DOI: 10.1002/app.1990.070390321
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cure kinetics of epoxy/imidazole resin systems

Abstract: SynopsisThe reaction kinetics for the cure of epoxy resins with imidazoles were determined from Fourier transform infrared spectroscopy and differential scanning calorimetry studies. The diglycidyl ether of bisphenol A and phenyl glycidyl ether were cured with various concentrations of 2-ethyl-4-methyl-imidazole ranging from 4.0 to 100.0 mol%. The first step in the curing process is the formation of epoxide/imidazole adducts. These adducts initiate the etherification reaction which crosslinks the resin. The ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
8

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 17 publications
2
63
0
8
Order By: Relevance
“…This value is much lower than the results obtained in previous work 5,19 in which E is also assumed to be constant and Fourier Transform Infrared Spectroscopy (FT IR) or DSC technique is used. Moreover, this value falls within the range of 34.3-63.84 KJ mol À1 obtained with Method II.…”
Section: Comparison Of the Two Methods And The Calculated Curing Kinementioning
confidence: 57%
See 3 more Smart Citations
“…This value is much lower than the results obtained in previous work 5,19 in which E is also assumed to be constant and Fourier Transform Infrared Spectroscopy (FT IR) or DSC technique is used. Moreover, this value falls within the range of 34.3-63.84 KJ mol À1 obtained with Method II.…”
Section: Comparison Of the Two Methods And The Calculated Curing Kinementioning
confidence: 57%
“…[1][2][3] The adducts were believed to be the catalyst that initiated the etherification reactions which cross-link the epoxy resins and determine the final properties of the network. Previous work 5 showed that the formation of adduct was necessary prior to the etherification reaction. Thus, low EMI-2,4 concentrations can be used to analyze the etherification reactions by suppressing the adduct formation.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Kinetic investigation is one of the most important applications of thermal analysis and has been widely conducted using isothermal or dynamic differential scanning calorimetry (DSC) technologies. [13][14][15] Kinetic studies are especially important when fillers are used to predict performances and design curing cycles for the epoxy composites. This ensures that the cured epoxy is able to respect the requirements of its end use applications.…”
Section: Introductionmentioning
confidence: 99%